Teachers’ attitudes towards student self-assessment and the use of assessment rubrics on an International Baccalaureate Diploma Programme. - Griffin, Aoife (2017)
This study investigates teachers’ perspectives on student self-assessment and the factors which influence if they use it in the classroom. It also examines rubric-referenced criterion as a potential assessment strategy at International Baccalaureate Diploma Programme. Quantitative and qualitative data were aggregated from a questionnaire and discussed by a focus group of my peers. Outcomes show that teachers have a positive attitude towards self-assessment strategies and consider it advantageous for students’ learning and performance. Moreover, self-assessment promotes critical thinking and independent learning, reflecting the IB ideology that teachers should support students to be inquiring and caring lifelong learners. Nonetheless, lack of time to design and implement a self-assessment curriculum and pressure to generate quantifiable data are considered potential obstacles. Finally, teaching self-assessment skills should be integrated into the curriculum in the early years of schooling.